Monitoring of Medication Compliance in Type 2 Diabetes Mellitus Patients with Media Adherence Pill Box Unit Daily Dose - Tresnowati, Gulita Indah; Kusuma, Ikhwan Yuda; Sunarti, Sunarti (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to affronts secretion disorders, affront action, or both. The management and management of DM is part of pharmaceutical care to reduce the causes of patient non-compliance in taking medication, resulting in complications. One way to prevent non-compliance is to provide a tool like Adherence Pill Box Unit Everyday Measurements. This study aimed to determine the effect of adherence pill box unit daily dose media in improving treatment adherence of type 2 DM patients. This study used an experimental method with the type of one gather pre-post test plan. Information was analyzed using the Wilcoxon rank test from the MMAS-8 questionnaire regarding medication adherence and blood sugar levels before and after being given the adherence pill box unit daily dose. The results of this study indicate the MMAS score – 8 sig. 0.002 < 0.05. This study concludes that there is an effect of Adherence Pill Box Unit Daily Dose media in improving medication adherence in patients, which has an impact on decreasing blood glucose levels in type 2 DM patients.